Polymeric Nanoneedle Arrays Mediate Stiffness‐Independent Intracellular Delivery. (1st September 2021) - Yoh, Hao Zhe; Chen, Yaping; Aslanoglou, Stella; Wong, Sherman; Trifunovic, Zlatan; Crawford, Simon; Lestrell, Esther; Priest, Craig; Alba, Maria; Thissen, Helmut; Voelcker, Nicolas H.; Elnathan, Roey
Abstract: Tunable vertically aligned nanostructures, usually fabricated using inorganic materials, are powerful nanoscale tools for advanced cellular manipulation. However, nanoscale precision typically requires advanced nanofabrication machinery and involves high manufacturing costs. By contrast, polymeric nanoneedles (NNs) of precise geometry can be produced by replica molding or nanoimprint lithography—rapid, simple, and cost‐effective. Here, cytocompatible polymeric arrays of NNs are engineered with identical topographies but differing stiffness, using polystyrene (PS), SU8, and polydimethylsiloxane (PDMS). By interfacing the polymeric NN arrays with adherent and suspension mammalian cells, and comparing the cellular responses of each of the three polymeric substrates, the influence of substrate stiffness from topography on cell behavior is decoupled. Notably, the ability of PS, SU8, and PDMS NNs is demonstrated to facilitate mRNA delivery to GPE86 cells with 26.8% ± 3.5%, 33.2% ± 7.4%, and 30.1% ± 4.1% average transfection efficiencies, respectively. Electron microscopy reveals the intricacy of the cell–NN interactions; and immunofluorescence imaging demonstrates that enhanced endocytosis is one of the mechanisms of PS NN‐mediated intracellular delivery, involving the endocytic proteins caveolin‐1 and clathrin heavy chain. The results provide insights into the interfacial interactions between cells and polymeric NNs, and their related intracellular delivery mechanisms. Abstract : Polymeric nanoneedle arrays of precise geometry are fabricated using commercially available polymers—polystyrene, SU8, and polydimethylsiloxane—to facilitate mRNA delivery into both adherent and suspension mammalian cells. By comparing nanoneedle substrates of identical topography but varying stiffness, this study decouples the effects on cell behavior of substrate stiffness and topography.